Midterm Blood Pressure Variability Is Associated with Poststroke Cognitive Impairment: A Prospective Cohort Study - Geng, Shan; Liu, Na; Meng, Pin; Ji, Niu; Sun, Yong’an; Xu, Yingda; Zhang, Guanghui; He, Xiaobing; Cai, Zenglin; Wang, Bei; Xu, Bei; Li, Zaipo; et al. (Frontiers in Neurology, 2017)
Objective The aim of this study was to investigate the relationship between blood pressure variability (BPV) and post stroke cognitive impairment (PSCI). Methods Seven-hundred and ninety-six patients with acute ischemic stroke were included in this study. Mid-term BPV was evaluated by calculating the standard deviation (SD) and coefficient of variation (CV, 100 × SD/mean) of systolic blood pressure (SBP) and diastolic blood pressure during the 7 days after stroke onset. Cognitive function was assessed using the Montreal Cognitive Assessment (MoCA) at admission and at all follow-up visits. Patients with MoCA scores <26 were considered to have PSCI. Results The incidence of PSCI reached its peak (72%) 3 months after stroke onset and decreased to 30.3% at 12 months post-stroke. After adjusting for covariables, the increase in the prevalence of PSCI at 3 months was independently associated with increases in the coefficient of variation of blood pressure during the 7 days after stroke ( odds ratios and 95%CI for patients in the second to fifth quintiles of SBP CV were 2.28(1.18,4.39), 2.33(1.18,4.62), 2.69(1.31,5.53), 4.76(1.95,11.67), respectively ). Sub-analysis of the MoCA scores revealed that the patients had impairments in visuoperceptual abilities and executive functions, as well as in naming and delayed recall (p < 0.05). Conclusions Mid-term blood pressure variability during the early phase of acute ischemic stroke is independently associated with post-stroke cognitive impairment, especially in the visuoperceptual, executive, and delayed recall domains.